2002
DOI: 10.1039/b201014c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Au nanoparticle–conductive polyaniline composite using H2O2 as oxidising as well as reducing agent

Abstract: We report a new method of synthesis of an Au nanoparticle-conductive polyaniline composite by using H2O2 both for reduction of HAuCl4 and polymerization of aniline in the same aqueous medium: the electrical conductivity of the composite has been measured to be two orders of magnitude higher than the polymer itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 16 publications
8
127
0
Order By: Relevance
“…By exploiting this property of starch, Sarma and Chattopadhyay (22) introduced such a strategy and reported on the results of the solubilization of polyaniline in water by encapsulation in starch as well as a polyaniline-gold-nanoparticle composite. The work is an extension of their previous work described in (15). TEM studies revealed that the gold particle sizes were in the range 10-20 nm.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…By exploiting this property of starch, Sarma and Chattopadhyay (22) introduced such a strategy and reported on the results of the solubilization of polyaniline in water by encapsulation in starch as well as a polyaniline-gold-nanoparticle composite. The work is an extension of their previous work described in (15). TEM studies revealed that the gold particle sizes were in the range 10-20 nm.…”
supporting
confidence: 52%
“…In the case of both methods, the size of the metal particles was dependent on the reaction time, reaction medium, and initial metal ion to polyaniline ratio. Chattopadhyay et al (15) have reported on the preparation of a gold-polyaniline composite material by using hydrogen peroxide as both the oxidizing and the reducing agent. This two step process involved the reduction of HAuCl 4 to Au nanoparticles in an aqueous medium followed by the polymerization of aniline which results in the formation of a composite of gold nanoparticles and conductive polyaniline.…”
mentioning
confidence: 99%
“…Minimum reflectance is reached in less than 2 min. The formation of gold nanoparticles due to reduction of HAuCl 4 by the hydrogen peroxide 12 is indicated by a rapid purple coloration of the solution. 13 We have confirmed nanoparticle formation by placing a droplet of the used etch solution onto a transmission electron microscopy ͑TEM͒ grid and imaging the 20-100 nm diameter particles.…”
Section: Nanostructured Black Silicon and The Optical Reflectance Of mentioning
confidence: 99%
“…The synthesis of AuNPs using the bis-pyridinium salt 3·2Br was attempted following a modification of the Brust-Schiffrin method [30] (see Supplementary Material Section 4 Table S2, entry 6). In the case of 4·2Br, the preparation of the AuNPs was attempted by a modification of the Turkevich method [29] using different reduction agents such as NaBH4 [34], H2O2 [35,36] or citrate [29] (see Supplementary Material Table S2, entries 7-10). In all cases, using 3·2Br or 4·2Br did not yield any AuNPs, as no formation of the typical red solution was observed, and a precipitate was visible in some cases.…”
Section: Resultsmentioning
confidence: 99%